Manipulation of Light Environment to Produce High-quality Poinsettia Plants - Mata, Diego Alejandro; Botto, Javier Francisco (American Society for Horticultural Science, 2020)
The phytochromes, a family of photoreceptors that maximally absorb red (R) and far-red (FR) light, play an important role in defining the architecture of the plant and consequently its value in the market. In this work, we evaluated the manipulation of light quality as an alternative to the use of plant growth regulators (PGRs) to produce poinsettia plants (Euphorbia pulcherrima Willd. ex Klotzsch) without affecting commercial quality parameters. ‘Freedom Red’ poinsettia plants were cultivated in two light environments characterized by different R/FR ratios in combination with or without one application of PGR. We used a photoselective film that significantly reduced the FR component of the light and a transparent film to obtain high and low R/FR ratios (5.7 and 1.1, respectively). Plants cultivated under a high R/FR ratio were shorter and more compact than those grown under transparent film. Other quality characters like bract and leaf area, dry weight, stem diameter, number of lateral branches, and plant width did not differ significantly between light treatments. Flowering time was slightly delayed in plants grown under a high R/FR ratio compared with those cultivated under the control treatment. Additive effects were detected between light quality and PGR factors indicating that light quality manipulation is an alternative strategy to reduce or to replace the use of PGRs in commercial production systems that usually require several PGR applications.